Optimizing the Impact of Incorporating Wind Energy on the Electric Grid - Carreras, B. A.; Barredo, J. M. Reynolds; Newman, D. E. (Journal of Strategic Innovation and Sustainability, 2020)
We investigate the impact of increasing the penetration of wind generation with real variability on the risk to, and robustness of, the power transmission grid using a dynamic model of the power transmission system (OPA). It is found that with different fractions and distributions of wind generation and central generation, varied dynamics and risk are possible. An important parameter is the fraction of the total power demand supplied by the wind generation. It is found that the risk has a minimum in fraction of wind power supplied, after which the risk increased as the wind penetration increases. Decreasing the number of central generators without decreasing their power supplied in general increases the risk after a critical minimum number of generators is reached.